Tailoring Low-Cost Granular Activated Carbons Intended for CO2 Adsorption - Prauchner, Marcos Juliano; Oliveira, Silvia da Cunha; Rodríguez-Reinoso, Francisco (Frontiers in Chemistry, 2020)
Physical adsorption on activated carbons has shown to be a very attractive methodology for CO2 separation from flue gas streams and biogas. In this context, the goal of this work was to prepare granular activated carbons intended for CO2 adsorption from an abundant and low-cost biomass residue (coconut shell) by using practical and cost-effective procedures. By the first time, parameters involved in chemical activation with dehydrating agents (H3PO4 or ZnCl2) and/or physical activation with CO2 were systematically screened in depth in order to obtain materials with improved volumetric CO2 adsorption capacities. Compared to the commonly used gravimetric basis, the data expressed on a volumetric basis are very important for industrial applications because they permit to estimate the efficiency of a fixed bed adsorption column. The work permitted to prepare activated carbons with a blend of relatively high gravimetric uptake and packing density, so that high volumetric CO2 uptakes were attained. The highest values were 2.67 and 1.17 mmol/cm3 for CO2 pressures of 1.0 and 0.15 bar, respectively. It is remarkable that the obtained results were similar to those reported by other authors for carbons chemically activated with KOH, the activation methodology that has been widely claimed to produce ACs with the best performances for CO2 capture, but which involves severe restrictions. Therefore, the present work can be considered a very important step in paving the way toward making CO2 capture an each time more interesting technology to reduce the emissions of anthropogenic greenhouse gases.